The Influence of Accountability Factors, Professionalism, and Auditor Experience on Audit Quality with Reward as a Moderation Empirical Study of Public Accounting Firm in Sulawesi, Maluku and Papua Regions - Sangkala, Masnawaty (PT. Maju Malaqbi Makkarana, 2024)
The purpose of this study is to determine the effect of auditor competence, independence, and experience on audit quality. This study is important because of the increasing demand from users of financial statements for quality audit reports. The population of this study were auditors working at a Public Accounting Firm domiciled in Bogor with a sample of 69 respondents. The sample was selected using the convenience sampling method. The data processing and analysis methods used were descriptive statistics, classical assumption testing, multiple linear regression testing and hypothesis testing. The data were tested using SPSS software version 25. The findings of this study indicate that the independent variables in this study, namely accountability, professionalism, and experience, simultaneously have a positive and significant effect on Audit Quality.